Parental Divorce: How to Ensure Child Support Rights are Protected? - Muh. Akbar Fhad Syahril; Hasrianti Hasrianti (Faculty of Law Andi Sapada Institute of Social Sciences and Business, 2024)
This study examines marriage law related to the implementation of child support rights after divorce, as well as legal remedies that can be taken by the child or his mother when the father does not fulfil his obligations by Law Number 1 of 1974 concerning Marriage. The type of research used is normative legal research, which analyzes case studies of decision number 134/Pdt.G/2023/PA. Bitter melon is qualitatively descriptive. The results of the study indicate the fulfilment of children's rights to support due to parental divorce at the Parepare Religious Court, based on a case study of decision number 134/Pdt.G/2023/PA. Pare, has not gone well because the ex-husband did not fulfil his obligations due to economic factors. On the other hand, the mother in this case felt that seeking justice through the courts would take too long and cost too much money, so she chose to finance her child's needs herself.